2016
DOI: 10.1189/jlb.5a0316-119rr
|View full text |Cite
|
Sign up to set email alerts
|

Protection of CD4+ T cells from hepatitis C virus infection-associated senescence via ΔNp63–miR-181a–Sirt1 pathway

Abstract: T cell dysfunction has a crucial role in establishing and maintaining viral persistence. We have previously shown a decline in miR-181a, which regulates CD4 T cell responses via DUSP6 overexpression, in individuals with hepatitis C virus (HCV) infection. Here, we describe accelerated T cell senescence in HCV-infected individuals compared with age- and sex-matched healthy subjects. Mechanistic studies revealed that up-regulation of transcription factor ΔNp63 led to the decline of miR-181a expression, resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 42 publications
4
28
0
Order By: Relevance
“…During chronic viral infections, however, T cells are always dysregulated and often non-responsive to vaccines 1 . We and others have previously reported that T cells from chronically virusinfected individuals are prematurely aged due to accelerated telomere erosion [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] , but the underlying mechanisms for T cell telomeric DNA damage remain unclear. Since Top2α is required to remove DNA supercoiling generated during cell proliferation, and Top2cc can become trapped during gene transcription to cause Top2cc-linked PDB due to TDP2 depletion 21,22 , we hypothesized that DNA topology in T cells may be affected during viral infections to trigger DDR as a mechanism of virus-induced immune evasion, and thus, persistent infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During chronic viral infections, however, T cells are always dysregulated and often non-responsive to vaccines 1 . We and others have previously reported that T cells from chronically virusinfected individuals are prematurely aged due to accelerated telomere erosion [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] , but the underlying mechanisms for T cell telomeric DNA damage remain unclear. Since Top2α is required to remove DNA supercoiling generated during cell proliferation, and Top2cc can become trapped during gene transcription to cause Top2cc-linked PDB due to TDP2 depletion 21,22 , we hypothesized that DNA topology in T cells may be affected during viral infections to trigger DDR as a mechanism of virus-induced immune evasion, and thus, persistent infection.…”
Section: Discussionmentioning
confidence: 99%
“…T cells play a critical role in control of viral infection. In studying the role of T cell dysregulation in viral persistence in humans, we and others have previously shown that chronic viral infections can cause premature T cell aging and immune senescence, as evidenced by the expression of aging markers and particularly, accumulation of DNA damage [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . However, the underlying mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Inconsistently, Serr's results showed that blocking miRNA‐181a promoted Treg proliferation in murine and humanized models in vivo . Zhou's report also suggested that transfection with miR‐181a precursor reduced the Treg numbers in chronic HCV infection . These inconsistent results suggested that miR‐181a may exert pro‐inflammatory or anti‐inflammatory effect in different backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…22 Zhou's report also suggested that transfection with miR-181a precursor reduced the Treg numbers in chronic HCV infection. 23 These inconsistent results suggested that miR-181a may exert pro-inflammatory or anti-inflammatory effect in different backgrounds. We also found that miR-181a regulated the function of Tregs through PI3K/Akt pathway, which was consistent with previous report.…”
Section: Discussionmentioning
confidence: 99%
“…CDH1 promoter is massively hypermethylated in genotype 1b HCV core protein-positive Huh-7 cells, in turn leading to reduced levels of CDH1 protein and increased levels of SIRT1 [76]. HCV-dependent alterations in SIRT1 function/activity have been shown by several studies performed in different cellular models [82][83][84][85][86]. In turn, SIRT1 is a well-established regulator of the circadian oscillation of clock-controlled genes in the liver, controlling fat metabolism, cell proliferation, and regeneration [87,88].…”
Section: Epigenetic Mechanisms Underlying the Interaction Between Virmentioning
confidence: 99%